Nordic walking jako szansa aktywizowania społeczeństwa = Nordic walking as a chance for the elicitation of the society - Paulina Jarecka; Tadeusz Fąk; Teresa Skrzypczyk (Kazimierz Wielki University, 2016)
Jarecka Paulina, Fąk Tadeusz, Skrzypczyk Teresa, Nordic walking jako szansa aktywizowania społeczeństwa = Nordic walking as a chance for the elicitation of the society. Journal of Education, Health and Sport. 2016;6(10):637-645. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.212211 http://ojs.ukw.edu.pl/index.php/johs/article/view/4083   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 21.10.2016.       Nordic walking jako szansa aktywizowania społeczeństwa Nordic walking as a chance for the elicitation of the society   Paulina Jarecka1, Tadeusz Fąk2, Teresa Skrzypczyk2   1 Katedra Pedagogiki Kultury Fizycznej, Akademia Wychowania Fizycznego we Wrocławiu 2 Instytut Turystyki, Wyższa Szkoła Bankowa we Wrocławiu   Słowa kluczowe: aktywizacja społeczeństwa, nordic walking Key words: elicitation of the society, nordic walking   Streszczenie W ciągu ostatniej dekady można zaobserwować wzrost zainteresowania aktywny mi fizycznie formami wypoczynku. Odpowiadając na te potrzeby urzędy miast, gmin, a także samorządy lokalne zaczęły wspierać i prowadzić różnego rodzaju projekty czy programy aktywizujące społeczeństwo w obszarze kultury fizycznej zapewniające możliwość bezpłatnego uczestnictwa. Jeden z obszarów tych inicjatyw dotyczy także popularyzowania nordic walking. W opinii autorów opracowania inicjatywy te zasługują na uznanie. Należy podkreślić, iż zgodnie z intencją ich pomysłodawców mają one służyć realizacji dwóch  głównych założeń, jakimi są: popularyzacja nordic walking w Polsce oraz jednocześnie aktywizacja społeczeństwa opierająca się na kształtowaniu kultury fizycznej. Na podstawie przeprowadzonej analizy należy stwierdzić, że wypełniają te właśnie cele oraz są podstawą w wyznaczaniu nowych kierunków zmian. Abstract Over the last decade, increased interest in physically active forms of rest could be observed. Responding to these needs city halls and local governments started to run and support various projects and programs eliciting society, while not requiring payment from participants. One of the areas of these initiatives refer also to popularization of nordic walking. In the opinion of the study's authors those initiatives deserve appreciation. It has to be pointed out, that in accordance to the intention of their originators, they should serve to achieve two main objectives: popularization of nordic walking in Poland and elicitation of society based on the development of the physical culture. Based on the analysis it can be said, that these initiatives fulfill those very goals. They are also fundamental thing to make chancing.